Atypical parkinsonism caused by Pro105Leu mutation of prion protein: A broad clinical spectrum. (February 2016) - Mano, Kagari Koshi; Matsukawa, Takashi; Mitsui, Jun; Ishiura, Hiroyuki; Tokushige, Shin-ichi; Takahashi, Yuji; Sato, Naoko Saito; Nakamoto, Fumiko Kusunoki; Ichikawa, Yaeko; Nagashima, Yu; Terao, Yasuo; Shimizu, Jun; et al.
Abstract : Objective: To delineate molecular and clinical characteristics of 3 families with PRNP P105L mutation, a variant of Gerstmann-Sträussler-Scheinker syndrome whose main motor symptoms were parkinsonism and/or involuntary movements. Methods: The causative mutation was first determined in the affected patients of family 1 using whole-exome sequencing, and then mutational analysis was extended to families 2 and 3. The clinical features of the patients of these 3 families were summarized. Haplotype analysis was performed using high-density single nucleotide polymorphism array. Results: The whole-exome sequencing revealed that the heterozygous mutation c.314C>T (p.P105L) in PRNP was the only known pathogenic mutation shared by the 3 patients of the family with autosomal dominant parkinsonism. We further identified the same mutation in patients of the other 2 families with autosomal dominant parkinsonism and/or involuntary movements. The clinical features of our patients with PRNP P105L mutation included various motor symptoms such as parkinsonism and involuntary movements in addition to progressive dementia. The clinical features in part overlapped with those of other forms of inherited prion diseases, such as fatal familial insomnia and Huntington disease-like type 1. The patients with PRNP P105L mutation shared a haplotype spanning 7.1 Mb around PRNP, raising the possibility that the mutations in the patients originated from a common founder. Conclusion: Most of the patients presented with parkinsonism in addition to progressive dementia. Although spastic paraparesis has been emphasized as the main clinical feature, the clinical spectrum of patients with PRNP P105L is broader than expected.